PENINGKATKAN KEAKTIFAN ASPEK AFEKTIF SISWA DALAM PEMBELAJARAN GERAK DASAR LOMPAT TINGGI DENGAN METODE PERMAINAN SISWA KELAS IV SD NEGERI BANYURADEN GAMPING SLEMAN - Mulyaarja dan Tri Ani Hastuti (Jurnal Pendidikan Jasmani Indonesia, 2015)
AbstractThe research problem was that there were some fourth grade students of SD Negeri Banyuraden, Gamping, Slemanwho found it hard to perform the high jump basic moves. The research objective was to improve the activeness of theaffective aspects from the fourth grade students of SD Negeri Banyuraden, Gamping, Sleman on the high jump basicmoves learning through the game method.This research was a classroom action research (CAR). The subjects werethe fourth grade students of SD Negeri Banyuraden, Gamping, Sleman with the total of 26 students. The assessmentinstruments were such as the observation sheets assessment for the improvement of affective aspects activenessof the students. The research method consisted of four main aspects, such as planning, action, observation, andreflection. The data analysis was using descriptive qualitative and descriptive quantitative analysis. The indicator forthesuccess was when the assessment results for the improvement of the affective aspects activeness of the studentsin the high jump learningthrough the game method had been gaining a score at ≥ 51 in other words it means that animprovementfor the activeness of the affective aspects of the students was in “good”.The results showed that it wasproved that the meeting in two cycles had been able to improve the activeness of the affective aspects of the studentsin the high jump basic moves learning on the fourth grade students of SD Negeri Banyuraden, Gamping,Sleman.Significant improvement occurred as it was compared to the initial data and the data of the first cycle. Improvementfor the activeness of the students’affective aspect in the high jump learning basic moves in the second cycle had theappropriate indicators of success. The score at “72” showed that the improvement for the activeness of the affectiveaspects of students was implemented really well.Keywords:Activeness, Affective, High Jump, Elementary School Students, GamesAbstrakPermasalahan penelitian adalah terdapat beberapa siswa kelas IV SD Negeri Banyuraden KecamatanGampingKabupaten Sleman yang sulit dalam melakukan gerak dasar lompat tinggi. Tujuan penelitian untuk meningkatkankeaktifan aspek afektif siswa dalam pembelajaran gerak dasar lompat tinggi siswa kelas IV SD Negeri BanyuradenKecamatan Gamping Kabupaten Sleman dengan metode permainan. Penelitian ini merupakan penelitian tindakankelas (PTK). Subyek penelitian adalah Siswa Kelas IV Banyuraden Kecamatan Gamping Kabupaten Sleman yangberjumlah keseluruhan 26 siswa. Instrumen penilaian berupa lembar observasi penilaian peningkatan keaktifanaspek afektif siswa. Metode penelitian tindakan kelas terdiri dari 4 aspek pokok, yaitu perencanaan, tindakan, tahappengamatan/observasi, dan refleksi.Analisis data secara deskriptif kualitatif dan kuantitatif. Indikator pencapaiankeberhasilan adalah apabila hasil penilaian peningkatan keaktifan aspek afektif siswa dalam pembelajaran lompattinggi dengan metode permainan telah mendapatkan skor ≥ 51 dengan arti lain peningkatan keaktifan aspek afektifsiswa berlangsung dengan “baik”. Hasil penelitian menunjukkan terbukti bahwa kenyataannya dalam pertemuan di duasiklus sudah dapat meningkatkan keaktifan aspek afektif siswa dalam pembelajaran gerak dasar lompat tinggi siswakelas IV SD Negeri Banyuraden Kecamatan Gamping Kabupaten. Peningkatan yang terjadi signifikan di bandingkandata awal dan data siklus satu. Peningkatan keaktifan siswa dalam pembelajaran gerak dasar lompat tinggi dalamranah aspek afektif di siklus dua telah sesuai indikator keberhasilan. Skor “72” menunjukkan Peningkatan keaktifanaspek afektif siswa berlangsung dengan baik.Kata kunci : Keaktifan, Afektif, Lompat Tinggi, Siswa SD, Permainan